Knowledge and practice of menstrual hygiene management among women living in a low-income neighbourhood, Karachi, Pakistan - Usman, Ghazala; Abbas, Kiran; Arshad, Rimsha; Muneer, Amna; Syed, Hiba S.; Iqbal, Anoosha; Dar, Farea N.; Anum, Urfa; Ahmed, Moiz; Tehreem, Khudija; Zulfi, Muhammad Hassan; Khan, Javeria (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The aim of the study was to determine the degree of awareness and practice of proper menstrual hygiene management among women living in low-income neighbourhood in Karachi, Pakistan. Methods: A cross-sectional study was conducted at the Bizerta Lines, Karachi between January and June 2019. All women of reproductive age were included in the study. Amenorrheic, menopausal, or women on birth control were excluded from the study. Degree of awareness and current practices pertaining to menstrual hygiene management were assessed through pro-forma. The study tool collected the participant’s knowledge, awareness, and misconceptions about menstruation. The factors affecting the quality of life during menstruation of women living in poor socio-economic conditions were also observed. Statistical Package for Social Sciences (SPSS v.23) was used to analyze the collected data. Results: Of the 338 participants, 82.5% had no knowledge of menstruation prior to their first menstrual period. Only a minority of the women knew that the source of menstrual blood was the uterus while 41.4% of the women incorrectly claimed that the menstrual blood and urine were expelled from the same orifice. More than half of the participants used disposable sanitary napkins (55.5%). 65% of the participants changed the absorbent at least 1 to 3 times a day. Conclusions: Most of the participants used disposable sanitary napkins. However, the basic knowledge of female anatomy and physiology behind menstruation was poor among women.